2019
DOI: 10.1002/dvg.23291
|View full text |Cite
|
Sign up to set email alerts
|

Ferulic acid improves self‐renewal and differentiation of human tendon‐derived stem cells by upregulating early growth response 1 through hypoxia

Abstract: We aimed to investigate the potential beneficial effect of ferulic acid (FA) on stemness of human tendon-derived stem cells (hTSCs) in vitro and to elucidate the underlying molecular mechanism.The self-renewal ability of hTSCs was evaluated by colony formation and cell proliferation was determined by CCK-8 kit. Adipogenesis, osteogenesis, and chondrogenesis were determined by Oil Red O, Alizarin Red, and Alcian Blue stainings, respectively. Relative mRNA levels of PPARγ, Col2A1, Acan, Runx2, HIF1α, and EGR1 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Moreover, EGR1 induces tenogenic differentiation in rabbit tendon stem cells [97]. EGR1 mediates the promoting effect of the anti-miR124 on collagen production in human tendon-derived stem cells [98] and the promoting effect of ferulic acid on self-renewal ability of human tendon-derived stem cells [99]. Consistent with the positive regulation of Col1a gene transcription by EGR1 observed both in vivo and in vitro, chromatin immunoprecipitation (ChIP) experiments show the recruitment of EGR1 to the tendon regulatory regions of the Col1a1 promoter in E18.5 limbs [73] and to Col1a1 and Col1a2 regulatory regions in adult Achilles tendons [76].…”
Section: Egr1 Roles In Connective Tissue Formation Homeostasis and Hmentioning
confidence: 99%
“…Moreover, EGR1 induces tenogenic differentiation in rabbit tendon stem cells [97]. EGR1 mediates the promoting effect of the anti-miR124 on collagen production in human tendon-derived stem cells [98] and the promoting effect of ferulic acid on self-renewal ability of human tendon-derived stem cells [99]. Consistent with the positive regulation of Col1a gene transcription by EGR1 observed both in vivo and in vitro, chromatin immunoprecipitation (ChIP) experiments show the recruitment of EGR1 to the tendon regulatory regions of the Col1a1 promoter in E18.5 limbs [73] and to Col1a1 and Col1a2 regulatory regions in adult Achilles tendons [76].…”
Section: Egr1 Roles In Connective Tissue Formation Homeostasis and Hmentioning
confidence: 99%
“…Qiu et colleagues investigated the beneficial effect of FA on stemness of human tendonderived stem cells (hTSCs) and demonstrated that FA treatment promoted proliferation, self-renewal, and multi-differentiation potential (adipogenesis, chondrogenesis, and osteogenesis) in hTSCs cultures, in a dose-dependent manner. However, the authors suggest that, in in vitro experiments, high FA concentration might present slightly adverse effects on cells suggesting that FA beneficial action falls within an optimal range [94]. Then, the critical involvement of HIF-1α in mediating the FA-elicited pro-stemness effect on hTSCs was further disclosed by a specific knockdown assay, which readily abolished this beneficial influence of FA [94].…”
Section: Other Hypoxic Mimetic Agentsmentioning
confidence: 99%
“…However, the authors suggest that, in in vitro experiments, high FA concentration might present slightly adverse effects on cells suggesting that FA beneficial action falls within an optimal range [94]. Then, the critical involvement of HIF-1α in mediating the FA-elicited pro-stemness effect on hTSCs was further disclosed by a specific knockdown assay, which readily abolished this beneficial influence of FA [94].…”
Section: Other Hypoxic Mimetic Agentsmentioning
confidence: 99%